2022
DOI: 10.1073/pnas.2211786119
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of quantum interference from single molecules to molecular cages and their monolayers

Abstract: The discovery of quantum interference (QI) is widely considered as an important advance in molecular electronics since it provides unique opportunities for achieving single-molecule devices with unprecedented performance. Although some pioneering studies suggested the presence of spin qubit coherence and QI in collective systems such as thin films, it remains unclear whether the QI can be transferred step-by-step from single molecules to different length scales, which hinders the application of QI in fabricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In this molecular family, molecule 4 with two para-substituted phenyl structures shows the highest transmission, followed by molecule 5 with one para-substituted phenyl and one meta-substituted phenyl structure, which is the typical structure demonstrating destructive quantum interference (DQI) that suppresses the conductance (transmission). 21,22 The transmission of the parallel molecular circuit 7 is located between that of molecule 5 and the lowest one (molecule 6) with two meta-substituted phenyl structures. This implies that, instead of the expected enhancement in the parallel molecular circuit, the conductance of the parallel molecular circuits constructed by the phenyl-convergent structure reveals an "averaged" result of all the conductances of individual channels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this molecular family, molecule 4 with two para-substituted phenyl structures shows the highest transmission, followed by molecule 5 with one para-substituted phenyl and one meta-substituted phenyl structure, which is the typical structure demonstrating destructive quantum interference (DQI) that suppresses the conductance (transmission). 21,22 The transmission of the parallel molecular circuit 7 is located between that of molecule 5 and the lowest one (molecule 6) with two meta-substituted phenyl structures. This implies that, instead of the expected enhancement in the parallel molecular circuit, the conductance of the parallel molecular circuits constructed by the phenyl-convergent structure reveals an "averaged" result of all the conductances of individual channels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Due to their small size and atomically precise structure, molecules exhibit quantum effects such as quantum interference (QI) even at room temperature. This has been demonstrated recently in closed-shell polycyclic aromatic hydrocarbons (PAHs). , For example, meta -connected pyrene shows a low conductance, which is a sign of destructive QI (DQI). The DQI in meta -connected anthraquinone (AQ) changes to constructive QI when the charge state of AQ changes, leading to an increase in conductance .…”
mentioning
confidence: 99%
“…9 Interestingly, the conductance of S2/S3 junctions was much lower than B2/B3 junctions, about 100fold less while comparing the S3 junction with the B3 junction. Please notice that the change of conductance tuned by the QI strategy was 43-fold (Figure S33) for p−p (1,2-di(pyridin-4yl)ethyne) and m−m (1,2-di(pyridin-3-yl)ethyne), 6.3-fold for p-DPB and m-DPB, 41 and 10-fold for p−p−p and m-p-m. 42 Venkataraman 29 and Hong 43 reported that destructive σinterference molecules Si2−Si222−Si2 and C 10 C 10 have a conductance around 10 −5.6 G 0 , which is nearly the same as our conjugated molecule S3 but with a longer molecular length. These results suggest that multiple fluorine substitution is an efficient strategy to suppress the conductance of molecules and that fluorine-substituted arenes are good candidates for singlemolecule insulators.…”
Section: Formation Of the Au−c Bond Via C−h Bondmentioning
confidence: 99%